If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + -4x = 16 + 6x Solving 36 + -4x = 16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 36 + -4x + -6x = 16 + 6x + -6x Combine like terms: -4x + -6x = -10x 36 + -10x = 16 + 6x + -6x Combine like terms: 6x + -6x = 0 36 + -10x = 16 + 0 36 + -10x = 16 Add '-36' to each side of the equation. 36 + -36 + -10x = 16 + -36 Combine like terms: 36 + -36 = 0 0 + -10x = 16 + -36 -10x = 16 + -36 Combine like terms: 16 + -36 = -20 -10x = -20 Divide each side by '-10'. x = 2 Simplifying x = 2
| -1(-1)= | | -x^2+2=x-4 | | -5(-2)+8(-3)= | | y^3-7y^2+8y+16=0 | | 8-(-8)+(-3)= | | -5(5)+4(4)= | | X*24=73.5 | | (3+x)(5x+7)=0 | | 7.63x^2+2.79x=5.32 | | -14-(-4)= | | -18+13= | | 6-2x=-10x+20 | | -12+(-13)= | | -11(-5)= | | -8+5-7= | | 4(-6)= | | 176=2x-4(5x-8) | | -45*(-5)= | | -8(3)= | | 14-(-8)= | | X*24=73 | | -5+(-10)= | | 76=-2x+4(-2x+4) | | -4w+7=10w+37 | | x+5x+(x+5)=180 | | 0=ln(2x^2) | | -5x-9=3x+23 | | c(x)=25.00-0.25x | | 2x-7=-25 | | onesixth=8 | | 147=3+3(8n-8) | | -20-7x=-10x+31 |